Indole-3-acetic acid in plant–microbe interactions - Duca, Daiana; Lorv, Janet; Patten, Cheryl L; Rose, David; Glick, Bernard R (Antonie van Leeuwenhoek, 2014)
Indole-3-acetic acid (IAA) is an important phytohormone with the capacity to control plant development in both beneficial and deleterious ways. The ability to synthesize IAA is an attribute that many bacteria including both plant growth-promoters and phytopathogens possess. There are three main pathways through which IAA is synthesized; the indole-3-pyruvic acid, indole-3-acetamide and indole-3-acetonitrile pathways. This chapter reviews the factors that effect the production of this phytohormone, the role of IAA in bacterial physiology and in plant–microbe interactions including phytostimulation and phytopathogenesis.